Penerapan "Padlet" dalam Pembelajaran Menulis Teks Eksposisi - Fitriani, Yeni (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
Learning to write exsposision texs is still difficult did by the teacher in teaching activity, because the students assume learning to write exposition text is boredÂ  and difficult, especially in starting writing. Based on this background, researcher conducted research with the Padlet application as media in learning to write exposition text. The objectives of this study are to find out the process of applying the Padlet application media, knowing students 'learning outcomes, knowing students' responses, and knowing the obstacles experienced when using the Padlet application in learning to write exposition text. The method used in this study is quasi-experimental or pre-experimental. The results showed that the process of applying Padlet application media made students feel happy, excited, enthusiastic, passionate, and active, interactive, responsive, in the learning process. Learning outcomes obtained an average score on the preliminary test of 61.93 and on the final test obtained an average score of 81.17. There are significant differences in learning outcomes in class X students of SMAN 2 Cianjur in learning to write exposition text after using the application Padlet. Students' responses regarding to the Padlet application responded positively. The obstaclesÂ  experienced in the learning process by using Padlet are network / signals that do not support, internet data plan, full memory storage of HP, and errors from the application.Keywords : Padlet Application, Learning Writing, Exposition Text.